NILAI-NILAI PENDIDIKAN AKHLAK DALAM NOVEL TUNGGU AKU DI SURGA (KARYA FAUZIAH FAUZAN EL MUHAMMADY) - Riskang Aj Pahruzi; Zulhaini Zulhaini; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2021)
The value of moral education consists of three words, namely, values, education and morals. Morals play an important role in human life. Good morals will distinguish humans from animals. Humans who have noble character, can maintain the glory and purity of their souls, can overcome the pressure of lust and cling to the joints of virtue. Given the very lack of morals of the younger generation today, this can be seen from several cases that have occurred. GoRiau.com There were 286 cases of HIV infection in the January-August 2020 period and 25 people died, dominated by men and this case occurred because of the prevalence of promiscuity among teenagers. This type of research, the author uses library research (Library Research). In the novel